Significance of palpitation among hypertensive patients receiving captopril - Marbut, Mossa M.; K. Rajab, Hassan; Al-Mahmood, Sinan (Tikrit University, 2009)
Captopril prevent the conversion of angiotensin 1 to II by inhibiting of peptidyl dipeptide carboxy hydrolase enzyme. Captopril is an angiotensin converting enzyme (ACE) inhibitors which is the treatment of hypertension. Hundred & eight hypertensive patients taking captoprill as a tablet 25 mg twice daily (47 men & 61 women). Each patient had a complete history detailed, physical examination, all patients were interviewed & full medical history was taken. All patients were questioned about the presence or absence of headache, palpitation, cough, flushing, chest pain, dysgeusia & tachycardia. Blood pressure & heart rate were measured for each patient each visit. In hypertensive men, 29 patients out of 47 (61.7%), hypertensive patients are diagnosed as suffering from palpitation. While in hypertensive women, 39 patients out of 61 women have palpitation after taking captopril for 3 months (64%). In regard to serum potassium, it was estimated in 51 hypertensive patients (27 with palpitation & 24 patients without palpitation). There is no significant difference in regarded to serum potassium between hypertensive patients with palpitation & hypertensive patients without palpitation. In hypertensive patients with palpitation, 9 patients out of 27 patients have hyperkalaemia (33.3%), (serum potassium more than 3 mmol/L). In hypertensive patients without palpitation, only 3 patients out of 24 patients have hyperkalaemia (0.125%). In hypertensive men, there are no significant differences between group with palpitation & patients without palpitation regarding blood pressure in both systolic & diastolic. Also, there is no significant difference regarding heart rate between group of patients with palpitation & group of patients without palpitation. Palpitation can be attributed to one of the three main causes. The first cause is hyperdynamic circulation which includes hypercapnia, pyrexia, thyrotoxicosis, anemia & pregnancy. The second cause is sympathetic overdrive include panic disorders, hypoglycemia, hypoxia, heart failure & mitral valve prolapse. While the third main cause is arrhythmias.